Asian Rhinoplasty with Rib Cartilage - Lee, Myung Ju (Semin Plast Surg, 2015)
An Asian rhinoplasty is one of the most popular procedures in plastic surgery. The anatomical characteristics of the Asian nose are quite different from those of other races, including low dorsum height, short columella, a thick soft tissue covering on the tip with flaccid lower lateral cartilage, and a sunken midface with relative protrusion of the mouth due to maxilla or premaxillary retrusion. For augmentation and lengthening of the nose, a silicone implant has been commonly used in Asian countries. However, many patients suffer from silicone-related complications, which induce soft tissue contraction and deform the already fragile nasal structure. Additionally, revision surgery is also increasing in frequency due to greater patient sophistication and higher expectation that the end rhinoplasty result to be more harmonious with the patient's overall facial structure. In these circumstances, a rhinoplasty using autologous rib cartilage, giving strong support and enough amount of the cartilage to correct deformed structure and midface skeletal retrusion. If properly performed with enough experience, a rib cartilage rhinoplasty will provide excellent and long-lasting results with low risk.